Are age-related differences between young and older adults in an affective working memory test sensitive to the music effects? - Borella, Erika; Carretti, Barbara; Grassi, Massimo; Nucci, Massimo; Sciore, Roberta (Frontiers in Aging Neuroscience, 2014)
There are evidences showing that music can affect cognitive performance by improving our emotional state. The aim of the current study was to analyze whether age-related differences between young and older adults in a Working Memory (WM) Span test in which the stimuli to be recalled have a different valence (i.e., neutral, positive, or negative words), are sensitive to exposure to music. Because some previous studies showed that emotional words can sustain older adults’ performance in WM, we examined whether listening to music could enhance the benefit of emotional material, with respect to neutral words, on WM performance decreasing the age-related difference between younger and older adults. In particular, the effect of two types of music (Mozart vs. Albinoni), which differ in tempo, arousal and mood induction, on age-related differences in an affective version of the Operation WM Span task were analyzed. Results showed no effect of music on the WM test regardless of the emotional content of the music (Mozart vs. Albinoni). However, as in previous studies, a valence effect for the words in the WM task was found with a higher number of negative words recalled with respect to positive and neutral ones in both younger and older adults. When individual differences, in terms of accuracy in the processing phase of the Operation Span task, were considered, only younger low-performing participants were affected by the type music, with the Albinoni condition that lowered their performance with respect to the Mozart condition. Such a result suggests that individual differences in WM performance, at least when young adults are considered, could be affected by the type of music. Altogether, these findings suggest that complex span tasks, such as WM tasks, along with age-related differences are less sensitive to music effects.